Spatial–Vertical Distribution of Microplastics Abundance and Characteristics in the Coastal Waters of Raha City, Muna Regency - Rahman, Annisa Syaesar; Afu, La Ode Alirman; Emiyarti, Emiyarti; Warsidah, Warsidah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Microplastics are emerging pollutants increasingly detected in coastal waters and may disrupt marine ecosystem functioning as well as pose potential risks to human health. This study aimed to analyze the spatial–vertical distribution of microplastic abundance and characteristics in the coastal waters of Raha City. Sampling was conducted at three stations representing an anthropogenic activity gradient: the harbor/fish landing port (Station I), the tourism–residential area (Station II), and the river mouth (Station III). At each station, samples were collected at three depths (surface, mid-water, and near-bottom) using a plankton net, then filtered and microscopically identified based on microplastic type and color. The results showed a consistent spatial gradient, with the highest mean abundance at Station I (5.58 particles/m³), followed by Station III (4.45 particles/m³), and the lowest at Station II (1.87 particles/m³). Vertically, microplastic abundance tended to be higher in the surface and mid-water layers than near the bottom, indicating the dominance of low-density particles remaining suspended in the water column. Microplastic characteristics were dominated by fibers across all stations, while black-colored particles were most frequently observed, accounting for >30% at each station. These findings confirm the strong contribution of fisheries–harbor activities and land-based waste inputs (particularly via the river mouth) as the main sources of microplastics in the study area. This study provides important baseline data on the three-dimensional distribution of microplastics in the coastal waters of Raha City and underscores the need to strengthen land-based waste management and regulate marine-related activities in the area.